Service first - Service Quality Institute (Bloomington, Minneapolis, : Service quality Institute)
Helping employees become the best they can be
vol. 1. Your key to customer satisfiction - vol. 2. Teamwork development - vol. 3. Handling complaints and the irate customer - vol. 4. The language of positive communication - vol. 5. Effective questioning and listening - vol. 6. Exceeding customer expectations - vol. 7. Value-added service - vol. 8. Effective telephone techniques - vol. 9. The art of satisfying customers - vol. 10. Service recovery - vol. 11. Empowerment - vol. 12. Total quality service
Keywords: Customer services; Customer satisfaction; Quality assurance